An overview of university students’ and graduates’ conceptions of language learning - Gómez, Juan Fernando; Díaz Larenas, Claudio (Círculo de Lingüística Aplicada a la Comunicación, 2020)
This empiric research attempts to identify the existing significant differences between A1 – B1 students and graduated professionals about language learning. A cross-sectional descriptive approach was employed with a sample of 658 participants. The BALLI instrument (Beliefs about Language Learning Inventory) was used to collect the data. Findings revealed that students prefer communicative language learning, consider English as difficult to learn, believe that vocabulary is the most critical aspect, and give a strong importance to translation and pronunciation. Graduated professionals conceive language learning as something traditional, ascribe it to a special ability, think it is easier to learn if you already know another language, feel the listening skill is easier than the speaking skill, disagree with translation and correction as strategies in language instruction.